CERTIFICATION FOR THE CONFORMITY OF ISO 9001 EQUIREMENTS AS A FIRST PHASE OF IMPLEMENTATION OF GOOD LABORATORY PRACTICE IN THE CENTER OF EXPERIMENTAL PHARMACOLOGY - I. A. Narkevich; E. V. Flisyuk; A. V. Moskvin; L. V. Shigarova; D. Y. Ivkin; A. S. Ivkina (Разработка и регистрация лекарственных средств)
The scope of certification of the quality management system is extended to research activities at the St. Petersburg Chemical and Pharmaceutical Academy. This allowed to to create more universal and effective system of organizing educational and research activities at the Academy when the integration of the process model mentioned and existing in the academy occurred. Based on this experience, management plans to confirm the compliance of activities of one of the structural units with GLP requirements. The authors demonstrated the feasibility of implementing a quality management system in accordance with the ISO 9001 standards as a strategic platform for preparing for the certification of preclinical research for compliance with the requirements of good laboratory practice (GLP).